2019
DOI: 10.1177/1751143719892784
|View full text |Cite
|
Sign up to set email alerts
|

Implementing target range oxygen in critical care: A quality improvement pilot study

Abstract: Background: Iatrogenic hyperoxaemia is common on critical care units and has been associated with increased mortality. We commenced a quality improvement pilot study to analyse the views and practice of critical care staff regarding oxygen therapy and to change practice to ensure that all patients have a prescribed target oxygen saturation range. Methods: A baseline measurement of oxygen target range prescribing was undertaken alongside a survey of staff attitudes. We then commenced a programme of change, wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…However, the intervention as a whole was judged successful and was accepted. The SOPs have proven to be sustainable and have results independent of the staff at work [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervention as a whole was judged successful and was accepted. The SOPs have proven to be sustainable and have results independent of the staff at work [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cousins et al 13 have previously highlighted the low rates of oxygen prescription and discussed the challenges for increasing prescription rates in clinical practice. Heartshorne et al 42 demonstrated sustained improvements in rates of oxygen prescription during their pilot study that utilized multiple methods designed to improve practice. Similar strategies need to be implemented across Australia to encourage change in doctor's prescription practices and improve administration and monitoring by nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus lag die SpO2 lediglich bei 15/68 (22 %) der Patienten mit O2-Therapie im Zielbereich, wobei in Großbritannien dieser Anteil bei 69 % lag 1 2 . In den letzten Jahrzehnten wurden weltweit mehrere Auditverfahren zur O2-Therapie durchgeführt, deren Ergebnisse zum Anlass genommen wurden, gezielte Schulungen des Personals vorzunehmen, welche im Verlauf die Qualität der O2-Therapie angehoben haben 16 18 19 20 21 22 .…”
Section: Diskussionunclassified